2011
DOI: 10.1051/parasite/2011183207
|View full text |Cite
|
Sign up to set email alerts
|

The antimalarial ferroquine: from bench to clinic

Abstract: Ferroquine (FQ, SSR97193) is currently the most advanced organometallic drug candidate and about to complete phase II clinical trials as a treatment for uncomplicated malaria. This ferrocenecontaining compound is active against both chloroquine-susceptible and chloroquine-resistant Plasmodium falciparum and P. vivax strains and/or isolates. This article focuses on the discovery of FQ, its antimalarial activity, the hypothesis of its mode of action, the current absence of resistance in vitro and recent clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
109
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(111 citation statements)
references
References 43 publications
0
109
0
2
Order By: Relevance
“…Indeed, in HIV-infected individ- uals, CQ was repeatedly reported to be effective in counteracting the deleterious immune activation associated with the disease (61). However, in clinical trials against influenza virus and chikungunya virus, CQ was rather disappointing (62,63). This could be due to high viral loads in vivo, poor penetration in specific tissues, and narrow therapeutic indexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in HIV-infected individ- uals, CQ was repeatedly reported to be effective in counteracting the deleterious immune activation associated with the disease (61). However, in clinical trials against influenza virus and chikungunya virus, CQ was rather disappointing (62,63). This could be due to high viral loads in vivo, poor penetration in specific tissues, and narrow therapeutic indexes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that FQ, a ferrocenic analog of CQ, is a promising inhibitor of HCV (15). This bio-organometallic compound is currently one of the most promising new candidate drugs in the antimalarial pipeline, and it is also in phase II clinical trials as a treatment for uncomplicated malaria (62). With IC 50 s of 0.91 M (this work) and 0.80 M (15) for B5 and FQ, respectively, these two compounds indeed show similar potency.…”
Section: Discussionmentioning
confidence: 99%
“…This has stimulated the interest in other compounds with more acceptable toxicity, such as ruthenium complexes (32)(33)(34)(35)(36). Effects of ruthenium compounds on some bacteria and parasites have been studied (37)(38)(39)(40)(41)(42)(43)(44)(45)(46). "Classical ruthenium complexes" contain heteroatom ligands (e.g., azole derivatives), and NAMI-A and KP-1019 have been evaluated in phase I clinical trials for cancer treatment (47)(48)(49).…”
mentioning
confidence: 99%
“…FQ was more active compared to CQ against all of the 19 CQ-R and CQ-S clones of P. falciparum examined in 11 different studies conducted by different laboratories. Importantly, no resistance to FQ was found among the CQ-R strains examined (Biot et al, 2011). At 8.3 mg/kg/d for four days, FQ was much more effective than CQ on rodent infected with malaria (Plasmodium berghei and Plasmodium vinckei).…”
Section: Learning From the Cq Hybrid Approach For Antimalarial Drug Dmentioning
confidence: 94%